Pediatric Granular Cell Tumor of the Breast: A Case Report and Review of the Literature - Nathan P. Heinzerling; Shannon M. Koehler; Sara Szabo; Amy J. Wagner (Case Reports in Surgery)
Objective. Granular cell tumors arise from neurogenic mesenchymal stem cells and can occur anywhere throughout the body. They rarely present as breast masses and should be included in the differential diagnosis of pediatric breast neoplasms. We report a rare presentation of a pediatric breast granular cell tumor and a review of the literature. Participant. A 15-year-old female presented with an enlarging breast mass. She underwent ultrasound imaging and excisional biopsy, which revealed a granular cell tumor. Granular cell tumors of the breast are difficult to diagnose using ultrasound and mammography due to numerous similarities to other breast masses. Histopathologic staining best differentiates breast granular cell tumors from other breast masses with their positive staining for S100, CD68, and neurospecific enolase. Conclusion. Although rare, granular cell tumors of the breast should be considered as a possible diagnosis for pediatric breast masses to allow for proper management and follow-up for these patients. Although rare, these tumors do have malignant potential necessitating a correct and timely diagnosis.